2017
DOI: 10.1017/s0140525x1600234x
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural constellation of deprivation: Causes and consequences

Abstract: Socioeconomic differences in behaviour are pervasive and well documented, but their causes are not yet well understood. Here, we make the case that a cluster of behaviours is associated with lower socioeconomic status (SES), which we call "the behavioural constellation of deprivation." We propose that the relatively limited control associated with lower SES curtails the extent to which people can expect to realise deferred rewards, leading to more present-oriented behaviour in a range of domains. We illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
300
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(313 citation statements)
references
References 524 publications
(693 reference statements)
11
300
0
2
Order By: Relevance
“…The evolutionarily selected coupling of environmental conditions with fast–slow LH trade‐off strategies continues to respond to current environments (Pepper & Nettle, ) and regulate human behavior and development (Del Giudice & Belsky, ). Research showed that the early childhood environment is especially pivotal in activating fast–slow LH strategies (Belsky, Steinberg, & Draper, ).…”
Section: Introductionmentioning
confidence: 99%
“…The evolutionarily selected coupling of environmental conditions with fast–slow LH trade‐off strategies continues to respond to current environments (Pepper & Nettle, ) and regulate human behavior and development (Del Giudice & Belsky, ). Research showed that the early childhood environment is especially pivotal in activating fast–slow LH strategies (Belsky, Steinberg, & Draper, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, under certain socio-ecological conditions, discounting the future can be a contextually appropriate response. To be more specific, developing a preference for the short-run may be fitness-maximizing in harsh and unpredictable environments (Becker & Mulligan, 1997;Daly & Wilson, 2005;Frankenhuis et al, 2016;Hill et al, 2008;Pepper, & Nettle, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When the future is uncertain or predictably harsh, therefore, the appropriate response might be to develop a short time horizon (Becker & Mulligan, 1997;Daly & Wilson, 2005;Pepper & Nettle, 2017) and to adopt strategies such as giving birth, as soon as possible, to the maximum number of offspring (Dickins et al, 2012;Johns et al, 2011;Nettle et al, 2011;Worthman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Further adaptationist arguments have been made regarding exposure to unpredictable and uncontrollable environments and a corresponding shift towards present oriented behaviour (Pepper & Nettle, 2017). Specifically, Pepper and Nettle (2017) make the claim that lower socioeconomic environments also contain cues to external mortality risk (i.e., risk of death from external sources such as violence) which cause changes in psychology in order to motivate 'adaptive' short-term strategies (e.g.…”
Section: A Genetically Informed Perspective On Causes Of Individual Dmentioning
confidence: 99%
“…Specifically, Pepper and Nettle (2017) make the claim that lower socioeconomic environments also contain cues to external mortality risk (i.e., risk of death from external sources such as violence) which cause changes in psychology in order to motivate 'adaptive' short-term strategies (e.g. earlier reproduction is adaptive in an environment where the future is uncertain).…”
Section: A Genetically Informed Perspective On Causes Of Individual Dmentioning
confidence: 99%